2010
DOI: 10.3109/0886022x.2010.502278
|View full text |Cite
|
Sign up to set email alerts
|

Renal glomerular alterations in patients with cancer: a clinical and immunohistochemical autopsy study

Abstract: Background: Membranous glomerulonephritis (MGN) can be found in patients with cancer as a paraneoplastic syndrome or it could be manifested clinically before tumor detection. The aim of this study was to evaluate the frequency and type of renal histopathological alterations in patients with malignancy that died without cancer treatment and were submitted to necropsy. Methods: Patient's demographical and clinical data collection and laboratory tests (serum creatinine and urine sample) were evaluated. Results: K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Lastly, those with cancers were excluded because previous study showed that they had different risk factors for CKD than other workers. 27 …”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Lastly, those with cancers were excluded because previous study showed that they had different risk factors for CKD than other workers. 27 …”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Some authors have reported a wide range of glomerular pathological changes and abnormal urinary sediments in these kind of patients. Membranous nephropathy, a clinical entity manifested by nephrotic syndrome, is highly associated with solid tumors (2). In our patient, there were symptoms and signs for acute nephritic syndrome but not for chronic glomerular disease.…”
Section: Discussionmentioning
confidence: 49%